2006
DOI: 10.1097/00019501-200605000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A new approach of primary angioplasty for ST-elevation acute myocardial infarction based on minimalist immediate mechanical intervention

Abstract: MIMI combined with maximized antithrombotic therapy results in immediate and sustained recanalization with a high rate of ST resolution in a majority of patients with ST elevation myocardial infarction. This approach allows one to postpone stenting in more stable conditions with a low rate of TIMI flow deterioration or to schedule more appropriate medical or surgical alternative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 36 publications
0
33
0
5
Order By: Relevance
“…However, several groups are reexamining this approach, and new treatment strategies are now emerging. Isaaz's 32 months. In the series as a whole, there were no acute events (ACS or sudden death).…”
Section: Discussionmentioning
confidence: 99%
“…However, several groups are reexamining this approach, and new treatment strategies are now emerging. Isaaz's 32 months. In the series as a whole, there were no acute events (ACS or sudden death).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that patients with a target lesion length >13.5 mm were 5.4-fold more likely to develop the no-reflow phenomenon than those with a target lesion length ≤13.5 mm. As suggested by Isaaz et al, 32 we advise treatment with low-dose thrombolytic drugs or glycoprotein receptor antagonists and postponing of PCI if adequate antegrade flow is achieved by initial predilatation in patients with high thrombus burden or a long target lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Isaaz et al 27) confirmed that this approach results in immediate and sustained recanalization, with a high rate of ST-segment resolution in about 80% of patients with STEMI, a percentage close to that observed after stent implantation.…”
mentioning
confidence: 75%